2007
DOI: 10.1677/joe.1.07097
|View full text |Cite
|
Sign up to set email alerts
|

Disordered follicle development in ovaries of prenatally androgenized ewes

Abstract: Exposure to excess androgens in utero induces irreversible changes in gonadotrophin secretion and results in disrupted reproductive endocrine and ovarian function in adulthood, in a manner reminiscent of the common clinical endocrinopathy of polycystic ovary syndrome (PCOS). We have recently identified an abnormality in early follicle development in PCOS which we suggested might be an androgenic effect. We propose that altered ovarian function in androgenized ewes is due to prenatal androgens not only causing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 44 publications
4
45
0
1
Order By: Relevance
“…Animal models have shown that prenatal androgen treatment induce accelerations of LH pulsatile release in primates (Abbott et al 2009), sheep (Forsdike et al 2007, Steckler et al 2009), and rodents (Foecking et al 2005), in accordance with the present results. Our observations confirm the concept that an early disturbance due to intrauterine androgen excess reprograms nervous tissue development of the fetus and irreversibly alters neuroendocrine function in female offspring.…”
Section: Discussionsupporting
confidence: 92%
“…Animal models have shown that prenatal androgen treatment induce accelerations of LH pulsatile release in primates (Abbott et al 2009), sheep (Forsdike et al 2007, Steckler et al 2009), and rodents (Foecking et al 2005), in accordance with the present results. Our observations confirm the concept that an early disturbance due to intrauterine androgen excess reprograms nervous tissue development of the fetus and irreversibly alters neuroendocrine function in female offspring.…”
Section: Discussionsupporting
confidence: 92%
“…For example, in vivo treatment with testosterone increases androgen receptor mRNA in granulosal and thecal cells in small antral follicles of primates, and the expression of androgen receptor mRNA is positively correlated with FSH receptor (FSHR) mRNA expression (Weil et al 1999). In addition, dihydrotestosterone (DHT) increases FSHR expression in preovulatory follicles in gilts (Cardenas et al 2002), and administration of testosterone or DHT to female rhesus monkeys and pregnant ewes (prenatally treated fetuses) stimulates primordial follicle initiation and increases growing follicle numbers and overall follicle survival , Steckler et al 2005, Forsdike et al 2007. During oocyte maturation and ovulation, androgens increase abundance of FSHR mRNA and number of preovulatory follicles and corpora lutea (Walters et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Srinivasan [27]. Prenatal exposure to androgen excess can lead to, as adults, disrupted ovarian cycles and abnormalities of early follicle development that mimic those observed in women with polycystic ovary syndrome [28][29][30][31]. It was reported that environmental factors can affect spermatogenesis at the level of germ and Stertoli cells and the composition of seminal fluid [32,33].…”
Section: Discussionmentioning
confidence: 99%